2017
DOI: 10.5935/1806-6690.20170008
|View full text |Cite
|
Sign up to set email alerts
|

Quality in papaya fruit produced with treated domestic sewage

Abstract: RESUMO -Objetivou-se, com a realização deste estudo, avaliar a qualidade físico-química e microbiológicas dos frutos do mamoeiro Tainung 1, produzidos mediante proporções de tempo de irrigação com água de abastecimento (AA) e esgoto doméstico tratado em tanque séptico seguido de filtros anaeróbios (AE). O delineamento experimental utilizado foi o de blocos casualizados com quatro tratamentos e seis repetições. Os tratamentos foram compostos por T1 (100% de AA mais adubação recomendada), T2 (67% de AA mais 33% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…These results were similar to those reported by Gomes Filho et al (2020a) and Gomes Filho et al 2020bwhen they analyzed lettuce and beans irrigated with treated wastewater. As well as the ones found by Batista et al (2017), who evaluated the microbiological quality of papaya fruit produced with treated wastewater. Libutti et al (2018) reported that the fecal coliforms populations in tomato and broccoli were not influenced by the types of water used for irrigation.…”
Section: Etc -Crop Evapotranspirationmentioning
confidence: 71%
“…These results were similar to those reported by Gomes Filho et al (2020a) and Gomes Filho et al 2020bwhen they analyzed lettuce and beans irrigated with treated wastewater. As well as the ones found by Batista et al (2017), who evaluated the microbiological quality of papaya fruit produced with treated wastewater. Libutti et al (2018) reported that the fecal coliforms populations in tomato and broccoli were not influenced by the types of water used for irrigation.…”
Section: Etc -Crop Evapotranspirationmentioning
confidence: 71%
“…De acordo com os resultados obtidos por Batista et al (2017), frutos do mamoeiro produzidos no experimento não apresentaram nenhuma contaminação por coliformes totais, bem como ausência de Salmonella sp, não apresentando nenhum risco para consumo in natura.…”
Section: Resultsunclassified
“…The drip irrigation system is an important technological alternative for the efficient use of water resources in semiarid environments. It saves water and electricity, increases crop yields and minimizes losses due to evaporation, percolation and runoff, when well designed and managed, (Kilic, 2020) and risks of microbiological contamination of agricultural products (Batista et al, 2017). The susceptibility to the clogging of emitters is a bottleneck that restricts the application and popularization of drip irrigation with wastewater.…”
Section: Introductionmentioning
confidence: 99%